2015
DOI: 10.1021/jacs.5b06562
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Single-Component Nickel(II) Polyethylene Catalysts via Phase Transfer of Fluorous Phosphine Ligands

Abstract: The nickel salicylaldiminato phosphine complexes [1,2,3-C6H3(9-anthracenyl)O(CH═N(2,6-C6H3(iPr)2)]Ni(Me)[P(4-C6H4R)3] (4; R = a, (CH2)2Rf8; b, (CH2)3Rf8; c, H (Rf8 = (CF2)7CF3)) are prepared from the corresponding phosphines 3a-c and nickel NCMe adduct (46-68%). These are applied as catalysts for ethylene polymerization in toluene and fluorous/toluene liquid/liquid biphasic mixtures. Under the latter conditions, the fluorous phosphines 3a,b that must dissociate to generate the active catalyst migrate to the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 30 publications
(21 reference statements)
0
28
0
Order By: Relevance
“…[50] Polymerizations are carried out under ac onstant pressure of 8atm using monophasic (toluene) and biphasic (toluene/ PFMC)c onditions. [51] As showni nF igure 8, appreciable phase-transfer activation occurred,w ith that for 27 a greatert han that for 27 b.T he phosphine ligand in the latter is, owing to the additional methylene groups,l ess fluorophilic.…”
Section: Other Catalysts or Reactionsmentioning
confidence: 91%
“…[50] Polymerizations are carried out under ac onstant pressure of 8atm using monophasic (toluene) and biphasic (toluene/ PFMC)c onditions. [51] As showni nF igure 8, appreciable phase-transfer activation occurred,w ith that for 27 a greatert han that for 27 b.T he phosphine ligand in the latter is, owing to the additional methylene groups,l ess fluorophilic.…”
Section: Other Catalysts or Reactionsmentioning
confidence: 91%
“…[19] These diverse applicationsc onvincingly validate the concept positedi n Scheme 1a nd show that it can be reliably exploited. In recent studies, the applicabilityo ft his protocolt on ickel-catalyzed ethylene polymerization was also demonstrated.…”
mentioning
confidence: 54%
“…[14] The perfluoroalkyl segmentsi n5 render it less basic than pyridine. Thus,t od rive the reaction, as eries of freeze/ pump/thaw cycles were conducted with fresh charges of CF 3 C 6 H 5 .A lthough most of the pyridine volatilized, trace amountso f5 remained, affording a9 3% yield of 7 of approximately 95 %p urity,a sa ssayed by the signal for Ru = CHPh in the 1 HNMR spectrum.N onetheless, the CF 3 C 6 F 11 /toluenep artition coefficient (39.8:60.2) could be determined by 19 FNMR spectroscopy,a sd escribed in the Supporting Information. This shows the complex to be predominantly lipophilic, suited for phase-transfer activation as in Schemes 1a nd 3.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2] The cooperativity effect engendered by dinuclear catalysts has been extensively investigated (Scheme 1, I). [6] By installing ap olyethylene glycol moiety into the salicylaldiminato ligand, Do et al showed that the properties of the corresponding nickel catalysts could be tuned using alkali cations during ethylene polymerization (Scheme 1, VI). [4] Theolefin polymerization process was modulated by the introduction of al igand second coordination sphere that interacted weakly with the growing polymer chain or the metal center (Scheme 1, III and IV).…”
mentioning
confidence: 99%